A PERCEPÇÃO DOS ALUNOS DOS CURSOS DE PÓS-GRADUAÇÃO LATO SENSU DA UNIJUÍ EM RELAÇÃO À SUA QUALIDADE - MÜLLER, BRUNA G.; VARGAS, GISLAINE L. D.; SOARES, JÚLIO C. V.; ZAMBERLAN, LUCIANO; WILM, MELISSA G. (Salão do Conhecimento, 2013)
Resumo